Spheno-Orbital Meningioma with Cavernous Sinus Extension - de Carvalho, Rodolfo Figueiredo; de Morais, Artur Nóbrega Lima; Olijnyk, Leonardo Desessards; Abrao, Adriana Azeredo Coutinho; Zanatta, Claudia; da Silva, Carlos Eduardo (Journal of Neurological Surgery Part B: Skull Base, 2021)
We present a case of a 37-year-old female, with progressive left eye proptosis and an extensive ipsilateral en plaque spheno-orbital meningioma, with diffuse involvement of the lateral wall of the cavernous sinus and the orbit.A cranio-orbital zygomatic approach was performed to reach all extension of the lesion. We made an extradural clinoidectomy and an extensive bone removal of the orbit, exposition of the superior and lateral walls of the cavernous sinus, unroofing of the optic canal, superior orbital fissure, foramen rotundum, and foramen ovale. We performed the peeling of the lateral wall of cavernous sinus with total removal and preservation of the cranial nerves anatomy and function.In this video, we illustrate the importance of the first time aggressive removal of such tumors. We also demonstrate the concept that secondary invasion of the cavernous sinus are suitable for removal with cranial nerve preservation.The link to the video can be found at https://youtu.be/GJmkqVa6jSs.